PENERAPAN MODEL PJBL PADA PEMBELAJARAN FILSAFAT HUKUM DALAM TATANAN HIDUP MASYARAKAT DI DESA - Hasibuan, Muhammad Khozali Husen; Siagian, Romadhansyah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
Project-Based Learning (PjBL) is an effective approach to increasing student engagement and building critical and problem-solving skills. This article discusses the development of the PjBL model in learning Legal Philosophy applied to the order of village community life. Legal Philosophy in this context plays an important role in understanding the legal principles that regulate social life in village communities, including customary norms and positive law. Through the PjBL approach, students are empowered to identify and solve legal problems faced by village communities, and develop solutions based on relevant legal theories. This study shows that the application of PjBL can improve students' understanding of legal philosophy concepts, strengthen their analytical and collaborative skills, and contribute to empowering village communities in facing legal challenges at the local level. These findings are expected to be a reference for innovation in learning legal philosophy that is more contextual and applicable in rural areas.